Analysis of the utilization of traditional medicine in Korea over 10 years (2013–2022): A repeated cross-sectional study using national health insurance data - Minjung Park; Yoon Jae Lee; Seungwon Shin (PLoS ONE, 2025)
Background This study aims to figure out the changes in traditional Korean medicine (TKM) utilization over the last decade, using the complete dataset of all claims submitted to the National Health Insurance (NHI) system in Korea. Methods This is a repeated cross-sectional study between 2013 and 2022. To observe TKM healthcare resources, we collected the number of TKM institutions, beds, and doctors. To observe changes in the utilization of TKM services, we collected the number of patients, claims, and medical expenses submitted to NHI. Data was analyzed according to inpatient/outpatient and hospitals/clinics. The compound annual growth rate was calculated. Results The growth was observed in the number of TKM hospitals, beds, and doctors. The changes in the claim count and the number of patients told us that TKM is going through a structural shift into hospital-centered services, even though the total number of patients utilizing TKM services decreased. The increase in TKM medical expenses was not merely a result of general inflation but reflects an increase in utilization of TKM services. Conclusions The key findings include a significant increase in inpatient services of TKM hospitals and medical expenses. The diversification of diagnostic and treatment methods highlights the evolving nature of TKM. Future research should focus on a more comprehensive study to examine the sociocultural and clinical factors influencing TKM utilization.